Screening of plants from the Brazilian Atlantic Forest led to the identification of Athenaea velutina (Solanaceae) as a novel source of antimetastatic agents - Almeida, Alisson A.; Lima, Graziela D. A.; Simão, Marcos V. R. C.; Moreira, Gabriela A.; Siqueira, Raoni P.; Zanatta, Ana C. [UNESP]; Vilegas, Wagner [UNESP]; Machado-Neves, Mariana; Bressan, Gustavo C.; Leite, João P. V. (Wiley, 2020)
Plant biodiversity is a source of potential natural products for the treatment of many diseases. One of the ways of discovering new drugs is through the cytotoxic screening of extract libraries. The present study evaluated 196 extracts prepared by maceration of Brazilian Atlantic Forest trees with organic solvents and distilled water for cytotoxic and antimetastatic activity. The MTT assay was used to screen the extract activity in MCF-7, HepG2 and B16F10 cancer cells. The highest cytotoxic extract had antimetastatic activity, as determined in in vitro assays and melanoma murine model. The organic extract of the leaves of Athenaea velutina (EAv) significantly inhibited migration, adhesion, invasion and cell colony formation in B16F10 cells. The phenolic compounds and flavonoids in EAv were identified for the first time, using flow injection with electrospray negative ionization-ion trap tandem mass spectrometry analysis (FIA-ESI-IT-MSn). EAv markedly suppressed the development of pulmonary melanomas following the intravenous injection of melanoma cells to C57BL/6 mice. Stereological analysis of the spleen cross-sections showed enlargement of the red pulp area after EAv treatment, which indicated the activation of the haematopoietic system. The treatment of melanoma-bearing mice with EAv did not result in liver damage. In conclusion, these findings suggest that A velutina is a source of natural products with potent antimetastatic activity.
Keywords: antimetastatic potential; Athenaea velutina; Brazilian Atlantic Forest; cytotoxic activity; phenolic compounds; plant extract screening